PENGARUH PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Tanti Jumaisyaroh Siregar (AXIOM : Jurnal Pendidikan dan Matematika, 2019)
The purpose of this study to determine: the effect of cooperative learning type of STAD to improve problem solving ability mathematics between students who were given cooperative learning type STAD with students and who were given direct learning. The type of this research is a quasi-experimental research by taking samples from the existing population. The variable of this research consist of independent variable that is cooperative learning type STAD while the dependent variable is problem solving mathematics ability of student. This research was conducted at SMP Swasta Al-Maksum Percut Sei Tuan. This research will be conducted in the even semester of the academic year 2017/2018. The population in this study is all students of SMP Swasta Al-Maksum Percut Sei Tuanand the sample in this study are students of grade eight by taking two classes that are VIII-4as experimental class and VII1-1as control class by random. Technique of collecting data in this research by using test. Test used is the problem solving mathematics ability test (pre test and post test). Data that have been collected then analyzed and performed hypothesis testing by using regression test. Based on the results of the analysis is obtained: there are effects of cooperative learning type STAD to improve student problem solving mathematics ability. Therefore, it is suggested that cooperative learning type STAD be used as an alternative for teachers to improve student problem solving mathematics ability.